The Influence of the Problem-Based Learning (PBL) Model on Students’ Active Participation in the Pancasila Education Subject at Elementary School - Asmaul Husna, Vinanda; Genisa, Tiara; Syadira, Riri; Maulidia, Rani; Maylanda, Refina; Ajma'in, Syazwana Nur Amalina; Reinita, Reinita; Salmaini, Salmaini (The Future of Education Journal, 2025)
Pancasila Education learning in elementary schools often faces challenges in increasing students’ active engagement. One method that can address this issue is the Problem-Based Learning (PBL) model, which focuses on solving real-world problems to encourage student participation. This study aims to examine the influence of the PBL model on students’ active involvement in Pancasila Education subjects. The research employs a literature review method by analyzing 10 scientific journals and research articles. Data collection was carried out through literature studies and document analysis, while data analysis applied a descriptive-qualitative approach to identify patterns of findings from various sources. The results indicate that the PBL model can enhance students’ active engagement in learning through discussion, collaborative problem-solving, and increased responsibility in the learning process. Furthermore, the implementation of PBL also supports students in developing critical thinking skills and understanding the values of Pancasila in everyday life.